The Vitality of the English-Speaking Communities of Quebec : From Community Decline to Revival - Bourhis, Richard Y. (2009)
The goal of this book is to provide a current portrait of the group vitality of the English-speaking Communities of Quebec. The enduring stereotype about the Anglophones of Quebec is that it is a pampered minority whose economic clout is such that federal or provincial support for the maintenance and development of its institutions is hardly necessary. This view of the privileged status of Quebec Anglos is widely held not only by the Francophone majority of Quebec but also by many leaders of Francophone communities across Canada. On the few occasions that Anglophones in the rest of Canada (ROC) spare a thought to the Anglophones of Quebec, either this idealised view of the community prevails, or they are portrayed as residents of a linguistic gulag whose rights are trampled on a regular and ongoing basis.
Keywords: Official Language Minority Community (OLMC)

On the Planned Decline of English Education in Quebec, Bill 96 and Some Ideological Clarifications - Bourhis, Richard Y. (Education and Vitality Forum, 2021)

Educational Vitality of the English-speaking Communities of Quebec : From Bill 101 to Bill 96 and Some Ideological Clarifications - Bourhis, Richard Y. (Coalition for the Future of English Education, 2022)

Evaluating the Impact of BIll 101 on the English-speaking Communities of Quebec - Bourhis, Richard Y. (Language Problems and Language Planning, 2019)

Some Notes on Quebec Government Laws Restricting Access to English CEGEPS and Proposed Fee Hikes for English Universities in Quebec - Bourhis, Richard Y. (QFHSA & COFFEE-QC & ComECH, 2023)

Perceptions de la migration interprovinciale des Canadiens anglais et Canadiens pour la vitalité des Québécois, Acadiens et Franco-ontariens - Bourhis, Richard Y.; Sioufi, Rana (2022)

Anglophone and Francophone Desire to Stay or Leave Quebec : A Study of Quebec-born Undergraduates in Montreal - Bourhis, Richard Y.; Sioufi, Rana (The Charter : Bill 101 and English-Speaking Quebec/La Charte : La loi 101 et les Québécois d’expression anglaise, 2021)

The Decline of the English School System in Quebec - Bourhis, Richard Y.; Foucher, Pierre (Canadian Institute for Research on Linguistic Minorities (CIRLM), 2012)
With the adoption of the Charter of the French Language by the Parti Québécois in 1977, Quebec Anglophones were most concerned about the erosion of their educational institutions resulting not only from the out-migration of Anglophones and Allophones to the rest of Canada (ROC), but also from the Bill 101 law stipulating that international immigrants to Quebec could no longer choose to send their children to English schools (Mallea, 1984). Thus, following Bill 101, Quebec Anglophones could no longer count on immigrants to maintain the demographic base necessary to keep open key English medium schools across the province (McAndrew, 2002). However by 1982, Anglophones, as English mother tongue “rights holders”, could now count on their right to English schooling in Quebec as enshrined in Article 23 of the Canadian Constitution.

Bill 103 : Collective Rights and the Declining Vitality of the English-speaking Communities of Quebec - Bourhis, Richard Y.; Foucher, Pierre (Quebec Community Groups Network (QCGN), 2010)
The first part of this brief deals with the declining vitality of the English speaking communities of Quebec (ESCQ) and the strength of the dominant Québécois francophone majority in the Province. We argue that a key premise of Bill 103 is based on the erroneous notion that the French language and its speakers are threatened in the Province of Quebec. This false premise brings the current government to draft Bill 103 with regulations making it virtually impossible for Allophone and immigrant children to be approved as pupils in the publicly funded English schools of the Province. As the past Education Minister Michele Courchesne stated on June 3rd 2010 “I won’t deny that the objective (of Bill 103) is to have as few as possible (approved)”.